Analytical Design, Simulation and Optimization of a 500 kW Doubly Fed Induction Generator - Ebrahim, Mostafa Haitham Ahmad; Kartal, Emin Tarik; Arabul, Fatma Keskin; Arabul, Ahmet Yigit (IEEE, 2025)
This paper presents the analytical design, simulation, and optimization of a 500 kW Doubly Fed Induction Generator (DFIG) intended for wind energy applications. The machine is initially designed using classical electromagnetic equations, followed by performance validation through Finite Element Analysis (FEA) using ANSYS Maxwell. A Genetic Algorithm (GA) is then employed to optimize key design parameters including slot geometry, flux densities, and current densities with the goal of minimizing losses and maximizing efficiency. The best analytical solutions are later validated through simulation, confirming the effectiveness of the combined design and optimization approach.
Keywords: DFIG; Finite Element Analysis; Genetic Algorithm; Electromagnetic Design; Wind Energy; Slot Geometry Optimization; Efficiency Improvement; DIRECT-DRIVE; WIND; SYSTEMS; Engineering